TiO2 AND TiO2/ACTIVE CARBON PHOTOCATALYSTS IMMOBILIZED ON TITANIUM PLATES - Winarti Andayani; Agustin Sumartono (Universitas Gadjah Mada, 2007)
Study of TiO2 and TiO2 active carbon photocatalyst was done. Immobilization was carried out by sol-gel process using titanium diisopropokside bis-acetylacetonato as titanium precursor. The catalyst was characterized using XRD and SEM. The activity of catalyst was tested using 10 ppm of pentachlorophenol (PCP) as a model of organic waste. The test was done by irradiating PCP solution using UV lamp and varying the catalysts of TiO2, and TiO2/C of 8/2 and 5/5. About 5 mL of sample was taken out at interval time of 1, 2, 4, 6, 8 and 10 h iradiation followed by the measurement of PCP residue and chloride ions. From the characterization results it is known that calcined TiO2 andTiO2/C of 8/2 and 5/5 have anatase structure and active as a catalyst. The activity results using PCP as an organic waste showed that combination of TiO2 and active carbon would increase the activity of the catalyst, but at high percentage of active carbon the performance of the photocatalyst decreased.